2020
DOI: 10.1097/opx.0000000000001466
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Crossover Trial Evaluating the Impact of Senofilcon A Photochromic Lens on Driving Performance

Abstract: SIGNIFICANCE The first contact lens to incorporate a photochromic additive was cleared by the U.S. Food and Drug Administration last year. Because any ophthalmic lens that absorbs visible wavelengths will reduce retinal illuminance, it is important to understand the impact of this new photochromic contact lens on vision and both daytime and nighttime driving performance. PURPOSE The purpose of this study was to evaluate the effect of senofilcon A photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…These results do suggest that a photochromic contact lens could improve visual quality even when worn in a motor vehicle or inside buildings. Buch et al 17 showed that, relative to a matched clear contact, the photochromic contact (the same control and test lens as used in this study) improved sign recognition at a distance by 19% during nighttime driving (i.e., conditions of minimal activation). The question of whether it is the actual change in filtering or some other quality of the lens is not clear.…”
Section: Discussionmentioning
confidence: 72%
“…These results do suggest that a photochromic contact lens could improve visual quality even when worn in a motor vehicle or inside buildings. Buch et al 17 showed that, relative to a matched clear contact, the photochromic contact (the same control and test lens as used in this study) improved sign recognition at a distance by 19% during nighttime driving (i.e., conditions of minimal activation). The question of whether it is the actual change in filtering or some other quality of the lens is not clear.…”
Section: Discussionmentioning
confidence: 72%
“…The recent introduction of photochromic lenses from Johnson & Johnson Vision (Jacksonville, FL, USA) may fill the gap left by the discontinuation of the MaxSight lenses, but to date no data on their use in athletes has been published. However, their value in reducing light scatter and improvements in other vision aspects have been presented [471][472][473]. Given the interest within the sports arena to even marginally improve any aspect of performance that provides a benefit to athletes, further development of tinted lenses for sports remains an area worthy of pursuit.…”
Section: Sports Enhancementmentioning
confidence: 99%
“…These disruptive lighting conditions include direct and reflected light from the sun, vehicle headlamps, and streetlights [18]. Current evidence suggests that drivers can safely wear photochromic contact lenses while driving during the day and at night [4]. A randomized, bilateral crossover trial found that both vision and driving performance were comparable between photochromic contact lenses, clear contact lenses, and photochromic spectacles.…”
Section: Vision Performance Itemmentioning
confidence: 99%
“…The U.S. Food and Drug Administration approved the Test lens in April 2018 [2], and studies have investigated aspects of its performance, including its effect on visual recovery, squint response, and driving [3,4]. Nonetheless, the literature is yet to report the subjective vision experience of patients fitted with this lens.…”
Section: Introductionmentioning
confidence: 99%